Growth performance and metabolic responses of Nile tilapia fed diets with different protein to energy ratios - Peres, H.; Freitas, J. M.A. [UNESP]; Carvalho, P. L.P. [UNESP]; Furuya, W. M.; Satori, M. M.P. [UNESP]; Oliva-Teles, A.; Pezzato, L. E. [UNESP]; Barros, M. M. [UNESP] (Elsevier, 2022)
The effect of dietary digestible protein to digestible energy (DP/DE) ratio on the growth performance and metabolic responses of Nile tilapia juveniles was evaluated. Five experimental diets were formulated with increasing DP/DE ratio (13.2, 15.5, 18.4, 20.0, and 22.6 mg kJ−1) and fed to eight replicates of Nile tilapia (initial body weight of 9.3 g) for 110 days. The apparent digestibility coefficients of the diets were determined in a parallel trial. Digestibility coefficients of dry matter, crude protein, and crude energy linearly decreased with increasing dietary P/E ratios. A quadratic effect of dietary DP/DE ratio on growth performance was observed, and maximum weight gain (g kg−1 day−1) or daily growth increment was attained with a dietary DP/DE ratio of 16.5 and 17.2 (mg kJ−1), respectively. Feed intake and energy retention (kJ ABW kg−1 day−1) linearly decreased, and feed efficiency linearly increased with increased dietary DP/DE ratio. The increase of dietary DP/DE ratio decreased the whole body, muscle, hepatic, and visceral lipid content and increased the fillet yield. The decrease of dietary DP/DE linearly increased nitrogen retention (% N intake) and whole-body lipid deposition through the reduction of amino acid catabolism (GDH and ALAT) and gluconeogenesis (FBPase) related enzymes and the increase of glycolysis (GK and HK) and lipogenesis- (G6PDH and ME) related enzymes. In conclusion, a dietary DP/DE ratio of 16.5–17.2 mg kJ−1 promoted the maximum growth performance of Nile tilapia juveniles. However, further studies are required to evaluate if a fine-tuning of the protein amino acid profile would allow a further reduction of the optimum dietary DP/DE ratio. Metabolic response to the decrease in dietary DP/DE levels suggested activation of glycolysis and lipogenesis and inhibition of amino acid catabolism and gluconeogenesis, highlighting the high capacity of Nile tilapia for metabolic utilization of dietary carbohydrates.
Keywords: Digestible protein/digestible energy ratio; Growth performance; Hepatic enzymes activity; Intermediary metabolism